Oscillatory behavior of solutions of second-order non-linear differential equations with mixed non-linear neutral terms - Hassan, Ahmed M.; Moaaz, Osama; Askar, Sameh S.; Alshamrani, Ahmad M. (Frontiers in Applied Mathematics and Statistics, 2024)
This study primarily seeks to expand upon these developments by encompassing neutral differential equations of mixed type, incorporating both delay and advanced terms, particularly in the case of the canonical operator. The presented results are derived through the application of the comparison method, the Riccati transformation, and the integral averaging technique. These methodologies lead to substantial improvements and extensions of existing results found in the literature. Additionally, illustrative examples are provided to demonstrate the practical implications of the developed criteria.